Single cell sequencing and computational findings reveal anti-estrogen receptor-positive breast cancer roles of formononetin - Bihui Li; Shuangxi Li; Ruihan Li; Menzhen Li; Zhaoquan Huang (Scientific Reports)
Abstract Breast cancer is the second leading cancer type in women, accounting for 11.6% of all cancers. Recently, its incidence has increased in younger individuals. Estrogen receptors (ERs) play important roles in the development and progression of breast cancer by controlling hormone signaling. Therefore, targeting ERs is one of the most promising therapeutic strategies for treating ER-positive breast cancer. High heterogeneity contributes to the tumorigenicity, metastatic ability, and therapeutic resistance of breast cancer. However, drug discovery studies at the single-cell level are lacking. In the present study, we used single-cell sequencing data analysis, together with a network pharmacology approach, to determine the targets and molecular mechanisms of formononetin in ER-positive breast cancer. Comparative single-cell sequencing analysis identified 3899, 3395, 333, 398, 398, and 17 differentially expressed genes in stromal cells, epithelial cells, fibroblasts, neutrophils, eosinophils, and macrophages, respectively, of ER-positive breast cancer compared with normal breast tissues. Further network pharmacology analysis highlighted the importance of formononetin targets in biological functions and signaling pathways related to immune and inflammatory responses, metastatic ability, metabolism, cell proliferation, and gland development in different ER-positive breast cancer cell types. For the first time, we used a systems biology approach to investigate the targets of formononetin and its anti-ER-positive breast cancer mechanisms at the single-cell level.